Mesenchymal Stem Cell-Based Therapy for Allergic Rhinitis - Liwei Sun; Jichao Sha; Cuida Meng; Dongdong Zhu (Hindawi Limited, 2020)
Allergic rhinitis (AR) is a prevalent disorder that causes a significant and often underestimated health burden for individuals and society. The current drug treatment cannot essentially deal with the regulation of the allergic reaction, while the allergic symptoms could be alleviated. Mesenchymal stem cells (MSCs) bear a variety of properties, such as the ability to differentiate into various cell lineages, to secrete soluble factors crucial for cell survival and proliferation, to migrate to the exact site of injury, and to modulate the immune response. Clinical studies have been extensively conducted in MSCs as the models for varieties of diseases such as neurological diseases. Due to their immunomodulatory properties, the MSCs have gradually been believed to become one of the promising strategies for AR treatments although so far the MSCs-mediated treatment for AR is still at animal experiments stage. Fully understanding the roles and mechanisms of MSCs immunomodulatory effects serves as the prerequisite that will be beneficial to the application of MSCs-based AR clinical treatment methods. In this review article, we highlighted the recent research advances and give a brief perspective in the future study of the MSCs-mediated therapeutic application in AR treatments.